Nutritional Composition of Selected Species of Sea cucumbers from Waters around Jaffna Peninsula, Sri Lanka - Ketharani, U.; Sivashanthini, K. (Faculty of Science, University of Jaffna, 2016)
Biochemical studies (protein, fat, moisture and ash) were done on five species of holothurians namely Holothuria leucospilota, Holothuria scabra, Holothuria spinifera, Stichopus naso and Thelenota anax, which were collected from the waters around Jaffna Peninsula during November 2013 to April 2014. Moisture, ash, protein and lipid contents of collected sea cucumbers were measured and recorded. The average moisture, protein, lipid and ash contents were 84.52±0.88%, 10.06±0.04%, 0.25±0.02% and 1.90±0.07% in H. leucospilota, 85.21±0.78%, 4.96±0.02%, 0.34±0.03% and 5.72±0.34% in H. scabra,79.19±0.86%, 8.22±0.43%, 0.27±0.05% and 9.22±0.23% in H. spinifera, 92.55±0.66%, 3.00±0.04%, 0.33±0.01% and 1.62±0.02% in S. naso and 89.92±1.33%, 3.14±0.03%, 0.40±0.02% and 2.90±0.01% in T. anax, respectively. Marked significant differences (p<0.05) were observed among sea cucumber species for the mean moisture, protein, lipid and ash contents. In comparison showed that H. leucospilota and H. spinifera possessed higher protein, T. anax possessed higher lipid and H. spinifera possessed higher ash contents than other investigated sea cucumber species. Among the five analyzed sea cucumber species, H. leucospilota is the most recommended as one of the healthiest food for human consumption as it has low fat content and high protein content.
Keywords: Sea cucumber; Nutritional composition; Jaffna Peninsula